Ontology: Examining Ibn Khaldun's Concept of Islamic Economics - Husnurrosyidah, Husnurrosyidah; Ihsan; Said, Nur; Islahuddin (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2026)
This study aims to determine the ontological basis of Islamic economics, particularly Ibn Khaldun's concept of Islamic economics. The research method used in this study is library research. The results of the study indicate that ontology in Islamic economics is based on divine revelation, which distinguishes it from conventional economics based solely on human rationality. This is manifested in basic principles such as the belief that natural resources are sufficient to meet human needs, the importance of limiting consumption, and the necessity of equitable distribution of wealth. These concepts aim to ensure that all economic activities are in line with the role of humans as caliphs on earth. Ibn Khaldun's thinking reinforces this ontological foundation. He sees economic phenomena, such as price mechanisms and the division of labour, as manifestations of divine order (sunnatullah). Ibn Khaldun also argues that labour is the true source of value. The wealth of a country comes from real productivity, and fair taxation is an instrument for realising justice (al-'adl) and the prosperity of civilisation (umran). Thus, both in general and through the thinking of Ibn Khaldun, Islamic economic ontology asserts that all economic activities must be subject to the ethics and objectives set by Allah SWT to achieve prosperity in this world and the hereafter.